A multicentre postal survey investigating the contribution of illness perceptions, coping and optimism to quality of life and mood in adults with muscle disease. (May 2014) - Graham, Christopher D; Weinman, John; Sadjadi, Reza; Chalder, Trudie; Petty, Richard; Hanna, Mike G; Turner, Chris; Parton, Matt; Maddison, Paul; Radunovic, Aleksandar; Longman, Cheryl; Robb, Yvonne; et al.
Objective: To replicate the finding that illness perceptions influence quality of life in adults with muscle disease and to explore the additional influence of coping and optimism on quality of life and mood. Design: A postal survey including questionnaires recording quality of life, mood, illness perceptions, optimism, coping and functional impairment. Setting: National Health Service muscle clinics in the United Kingdom. Participants: A convenience sample of adults with muscle disease. Interventions: Not applicable. Main outcome measures: Individualised Neuromuscular Quality of Life Questionnaire, Hospital Anxiety and Depression Scale. Results: A total of 226 completed questionnaires were returned. Although functional impairment explained most of the variance in three out of eight quality of life domains, psychological factors explained greater amounts of variance (between 19% and 52% of variance) in all other quality of life domains and in both mood domains (between 45% and 48% of variance). Overall, illness perceptions explained much of the variance in quality of life and mood score (between 5% and 37% of variance), while coping (up to 8% of variance) and optimism (up to 15% of variance) explained smaller amounts of variance. Conclusion: The results confirm that illness perceptions are associated with quality of life in muscle disease and suggest that they also influence mood. The addition of optimism and coping variables into the analysis yielded small increases in the proportions of variance in quality of life and mood which were explained. These results have implications for the composition of future psychological interventions.